Gut microbiome dynamics and functional shifts in healthy aging: insights from a metagenomic study - Ai, Xu; Huang, Chenchen; Liu, Qiongrong; Duan, Rui; Ma, Xu; Li, Linzi; Shu, Zitan; Miao, Yuanxin; Shen, Hexiao; Lv, Yongling; Jiang, Zhiwei; Luo, Hong; et al. (Frontiers in Microbiology, 2025)
IntroductionPopulation aging represents a significant challenge in contemporary society. The gut microbiome plays a critical role in maintaining host health and physiological functions, and its alterations with advancing age are closely associated with the process of healthy aging.MethodsThis study conducted a comprehensive analysis of the gut microbiome in hundred healthy elderly individuals (aged ≥60) residing in Changshou Town, Zhongxiang City, Hubei Province, utilizing metagenomic sequencing technology. The primary objective was to investigate the changes in the gut microbiome and its potential functions during the latter stages of life. Participants were categorized into three distinct age groups: the Young-Old group (YO, ages 60-74), the Middle-Old group (MO, ages 75-89), and the Long-Lived Old group (LO, ages 90-99).ResultsThe findings indicate that the diversity of the gut microbiome tends to diminish with age. However, a significant reversal was observed among healthy longevity elderly individuals. Our analysis specifically focused on the trends in the alterations of gut microbiome species and their potential functions as age increases, revealing that the changes in major differential functions closely align with the trends in major differential species, demonstrating a strong positive correlation. The YO group exhibited a more diverse array of differential microbial characteristics and functional traits. Notably, there was a significant enrichment of Bacteroides stercoris in the YO group, which displayed a continuous decline with age, alongside a marked enrichment of pathways associated with xenobiotic biodegradation and metabolism. Furthermore, species significantly linked to aging-related pathways, such as oxidative phosphorylation, were identified through species functional correlation analysis. Specifically, Collinsella bouchesdurhonensis and Prevotella stercorea were enriched in the LO and YO groups, respectively. In total, we successfully obtained two hundred and thirty eight high-quality bins through metagenomic assembly, which included the identification of four species with 100% completeness, as well as the genomic information of the Methanobrevibacter smithii A across all groups.DiscussionThis study characterizes the age-associated trends in gut microbiome composition and function during later-life healthy aging, providing exploratory insights that may inform future microecological intervention strategies, pending validation in longitudinal studies.